Effectiveness evaluation of mood disorder treatment algorithms in Brazilian public healthcare patients - Lima,Ana F. (2018)
Objective: To assess the effectiveness of three mood disorder treatment algorithms in a sample of patients seeking care in the Brazilian public healthcare system. Methods: A randomized pragmatic trial was conducted with an algorithm developed for treating episodes of major depressive disorder (MDD), bipolar depressive episodes and mixed episodes of bipolar disorder (BD). Results: The sample consisted of 259 subjects diagnosed with BD or MDD (DSM-IV-TR). After the onset of symptoms, the first treatment occurred ∼6 years and the use of mood stabilizers began ∼12 years. All proposed algorithms were effective, with response rates around 80%. The majority of the subjects took 20 weeks to obtain a therapeutic response. Conclusions: The algorithms were effective with the medications available through the Brazilian Unified Health System. Because therapeutic response was achieved in most subjects by 20 weeks, a follow-up period longer than 12 weeks may be required to confirm adequate response to treatment. Remission of symptoms is still the main desired outcome. Subjects who achieved remission recovered more rapidly and remained more stable over time. Clinical trial registration: NCT02901249, NCT02870283, NCT02918097